Uma proposta de sequência didática: conhecendo os quelônios da Amazônia - SOUSA, Ana Caroline Silva (2023)
The Amazon is considered the region with the greatest diversity of species of turtles, being this one of the groups of vertebrates most threatened with extinction due to factors that contribute to the decline of species such as the loss of aquatic habitats, the use for medicinal purposes, as an animal and as a food resource. Bearing in mind that the use of chelonian for undue purposes will consequently bring losses for the species, as well as for the ecological balance, this proposal for a didactic sequence for the 7th year of Elementary School, consisting of eight moments to be developed in twelve classes, aims to objective is to study the species of the two groups of turtles, tortoises and tortoises existing in the Xingu / Pará region, as well as the study of the preservation and conservation of these species.